Kognitif, lansia, Kualitas Hidup PENGARUH FUNGSI KOGNITIF TERHADAP KUALITAS HIDUP LANSIA DI POSYANDU LANSIA SRIKANDI KELURAHAN GADINGKASRI KECAMATAN KLOJEN MALANG: EFFECT OF COGNITIVE FUNCTION ON LIFE QUALITY OF ELDERLY IN POSYANDU LANSIA SRIKANDI KELURAHAN GADINGKASRI KECAMATAN KLOJEN MALANG - Astutik, Nanik Dwi (Jurnal Keperawatan Malang, 2017)
Abstract The aging process experienced by elderly will bring some changes in some aspects such as physical, psychosocial and intellectual capacity of the elderly where it is closely related to changes in cognitive function in the elderly. A good cognitive function is needed to improve the quality of life especially optimizing functional status, general circumstances, better productivity, creativity, and happiness. Research goal is to identify the effects of cognitive function on quality of life in the elderly. Cross sectional design was used, and 66 elderly respondents were obtained. Mini Mental State Examination (MMSE) and World Health Organization Quality Of Life (WHOQOL) – Bref was used to obtain data. Regresi Linier Sederhana analysis was used to analyze the data. Analysis shows that p = 0.000 (<0.05) and it could be inferred that there was effect of cognitive function on quality of life in the elderly. The existence of this influence is caused by cognitive function affects the ability among the elderly to perform normal daily activities in both physical activity and social activities Keywords : Cognitive Function, Quality of Life, Elderly